(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is customary to consider human capital as a set of knowledge, abilities, skills, talents contained in a person in terms of the possibilities of their use to meet human needs and the progress of society. From the moment of the formation of the theory of human capital to the present day, its supporters pay special attention to issues related to the correctness of the assessment of human capital.